Antibacterial activity of actimycetes against multiresistant Escherichia coli and Staphylococcus aureus isolated from a hospital - Ortega Bastidas, Luis Alberto; Castillo Arteaga, Roger David; Gomez Arrieta, Jenny Dimelza; Fernández Izquierdo, Pablo; Burbano Rosero, Edith Mariela (Universidad y Salud, 2021)
Introduction: Antimicrobial resistance (AR) is a public health problem that reveals the diminished efficacy of these agents in the prevention and treatment of an increasingly larger number of pathologies. Actinomycetes are an important bacterial producer group of metabolites that are active against pathogens. Objective: To isolate actinomycetes from the tropical forest of Nariño (Colombia), which have the potential to produce inhibitory metabolites against multi-drug resistant bacteria. Materials and methods: Soil samples were taken from the Humid Tropical Forest of the Río Ńambí Natural Reserve and analyzed through microbiological and molecular assays. In vitro production of secondary metabolites was first stimulated, followed by the assessment of the inhibitory effect of these extracts against multi-drug resistant Escherichia coli and Staphylococcus aureus. Results: 11 presumptive isolates were obtained, confirming that four of them corresponded to the Streptomycess sp. genus. The bacterial isolate P3772 was identified as the one with the highest inhibitory effect against multi-drug resistant E. coli and S. aureus. Conclusions: All the actinomycetes evaluated presented antibacterial activity. The isolate P3772 stands out, which inhibited both E. coli and S. aureus. The compounds associated with this antibacterial activity will be characterized in future studies.